Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae) - Prieto, Carlos E.; Wijnhoven, Hay (European Journal of Taxonomy, 2020)
Recent studies have shown that the speciose Holarctic genera of Leiobunum C.L. Koch, 1839 and Nelima Roewer, 1910 are polyphyletic taxa, and therefore, the traditional diagnostic characters for these European genera of Leiobuninae Banks, 1893 (respectively, the presence or absence of tubercle rows on leg coxae) are unsuitable. We present the description of Leiolima iberica gen. et sp. nov., a new endemic harvestman from the north-western part of the Iberian Peninsula. The newly established genus shows intermediate characters between Leiobunum and Nelima. In addition, the new genus is characterized by shorter legs compared to Leiobunum and the presence of trichomes on all leg femora and pedipalpal patellae, a structure that is absent in all other western Palearctic genera of the subfamily Leiobuninae.